Peran Tekanan Teman Sebaya Terhadap Perilaku Disruptif Pelajar SMA Di Kabupaten Jember - Ulum, Misbahul; Syakarofath, Nandy Agustin; Widyasari, Dian Caesaria; Latipun, Latipun (JURNAL PSIKOLOGI, 2024)
Peer environment is a protective factor and risk factor for various possible adolescent behavioural problems. This study aimed to identify the role of peer pressure on the emergence of adolescent disruptive behaviour. The research method used is quantitative non-experimentation. A total of 279 participants were subjected to research using multistage random sampling. The study subjects were spread across seven Public and Private High Schools in Jember Regency with details of 203 female students and 76 male students aged 15-17 years. The research instrument used is the NPPI (Negative Peer Pressure Inventory) scale to uncover the role of peer pressure and the SDQ (Strengths Difficulties Questionnaire) to uncover disruptive behavior. The data was then analyzed using simple linear regression techniques and multiple linear. The results showed a positive role in peer pressure on adolescent disruptive behavior (β= 0.221, p<0.05). The two most significant aspects of peer pressure roles that play a role in disruptive behavior are involvement with family (β= 0.198, p< 0.05) and misconduct or deviance (β =0.192, p<0.05). It is thus understood that the higher the role of peer pressure can lead to a greater chance of adolescents bringing up disruptive behaviour.